2005
DOI: 10.1097/01.ta.0000158269.68409.1c
|View full text |Cite
|
Sign up to set email alerts
|

Can Near-Infrared Spectroscopy Identify the Severity of Shock in Trauma Patients?

Abstract: Decreased thenar muscle tissue oxygen saturation reflects the presence of severe hypoperfusion and near-infrared spectroscopy may be a novel method for rapidly and noninvasively assessing changes in tissue dysoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
3
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(169 citation statements)
references
References 21 publications
6
154
3
6
Order By: Relevance
“…Preliminary reports regarding regional CO 2 measurement in sensible microvascular beds, as manifestation of hypoperfusion, are promising [71][72][73]. Measurement of oxygen tension or saturation in certain tissues has permitted the identification of occult hypoperfusion in animal studies and in some limited clinical experiences published [71,[74][75][76][77][78]. Unfortunately, these methods have not been fully evaluated, and none of them has reached widespread use.…”
mentioning
confidence: 99%
“…Preliminary reports regarding regional CO 2 measurement in sensible microvascular beds, as manifestation of hypoperfusion, are promising [71][72][73]. Measurement of oxygen tension or saturation in certain tissues has permitted the identification of occult hypoperfusion in animal studies and in some limited clinical experiences published [71,[74][75][76][77][78]. Unfortunately, these methods have not been fully evaluated, and none of them has reached widespread use.…”
mentioning
confidence: 99%
“…A prospective non-randomized observational human study of volunteers and patients admitted to a level 1 trauma centre established a normal range for thenar eminence StO 2 and showed it could be used to identify the patients in severe shock. However, this study did not attempt to examine the effect of resuscitation on StO 2 [82]. A prospective, blinded cohort study of patients admitted to a level 1 trauma centre has demonstrated that initial StO 2 values correlated with shock index and was predictive of the development of subsequent multi-organ dysfunction syndrome [83].…”
Section: Point Of Care Testing and Monitoring In Trauma Resuscitationmentioning
confidence: 99%
“…The NIRS devices are usually portable, permitting bedside monitoring. There have been recently exploratory studies using NIRS for shock monitor [4,[9][10][11][12][13][14][15]. Some of them were carried out on animal models [12,13] or healthy human subjects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them were carried out on animal models [12,13] or healthy human subjects [14]. A few were performed in patients either invasively with optical sensors inserted into subcutaneous and intramuscular sites [4,15] or noninvasively with optical probes placed on the peripheral muscles [9][10][11]. However, shock usually results in a poor peripheral blood circulation [5], leading to an insensitive measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation